Analisis Labeling Dadap Ceng In Sebagai Kawasan Prostitusi Di Kabupaten Tangerang - Raya, Sylvia Mugniy; Priyana, Puti (Jurnal Ilmiah Wahana Pendidikan, 2024)
more people give nicknames or labels to him, the person or group will deviate from the norm. Labeling or naming something comes from other people's reactions. Which means, that there are people who give names, definitions, nicknames, labels to individuals or actions that are considered negative for that person. In the Dadap Ceng In area which is located in Dadap Village, Kosambi Subdistrict, Tangerang Regency, Banten, is an area that is the place or origin of the behavior of people who deviate from the norms that should exist in the surrounding community. The Dadap Ceng In area is the largest place of prostitution in Tangerang Regency, which in this case prostitution is something that becomes a deviation in norms and law. criminal law that categorizes prostitution as a criminal act only to the intermediary. The Criminal Code never mentions or limits the provisions on prostitution, but it explicitly refers to sex trafficking in relation to intermediaries or pimps.